Downward mobility : the form of capital and the sentimental novel - Binhammer, Katherine, 1962- (Book collections on Project MUSE., 2020)
"Binhammer uses the methodologies of contemporary critical finance studies and narrative theory to argue that the myth of downward mobility is as central to the cultural history of capitalism as the myth of upward mobility. By exploring the relationship between economic growth and financial failure, she demonstrates how stories of downward mobility in eighteenth-century sentimental novels are not simple tales about the losers of capitalism but help manage the crises and speculative collapses that are inevitable to capital's circulation"--